Deep rolling effect on fatigue behavior of austenitic stainless steels. (February 2017) - Muñoz-Cubillos, J.; Coronado, J.J.; Rodríguez, S.A.
Highlights: The most important parameter to increase the hardness is the applied force in DRT. AISI 304 presents a better increase of fatigue strength after DRT than AISI 316. Metallurgical effects are responsible by the differences in both steels after DRT. Abstract: In the present study, the effect of deep rolling on the fatigue behavior of two austenitic stainless steels susceptible to strain hardening (AISI 304 and AISI 316) was investigated. The effect of the force and the deformation velocity, on the surface hardening and the final roughness produced by deep rolling treatment, were analyzed using a device built for this purpose. The microstructure of the materials was characterized by optical microscopy, the fracture surfaces were characterized using scanning electron microscopy, the residual stresses and microstructural changes produced by the deep rolling method were characterized by X-ray diffraction. Results show that the deep rolling produces increase in hardness, volume fraction of martensite and compressive residual stresses that increase the fatigue strength of both steels. Also, it was observed that at high cycle fatigue, the AISI 304 stainless steel presents a better fatigue response after deep rolling treatment than the AISI 316. This behavior is associated with a higher resistance to fatigue crack nucleation and growth rate due to metallurgical effects, such as deformation twins and a greater increase in the volume fraction of martensite.